Primary Care-based Evaluation of Patient Education for Osteoarthritis of the Knee - Triggs, E.; Victor, C.; Ross, F.; Axford, J. (Methods of Information in Medicine, 2000)
Primary healthcare research in the UK has expanded in conjunction with the wider agenda of a primary care led National Health Service (NHS). This reflects international reconsideration of the place of primary healthcare within national healthcare systems. However the role and standing of research in primary care tends to be marginal and less influential than that originating in research establishments or medical schools pursuing biomedical investigations. There are many reasons for this, some of which this paper attempts to elucidate. We address the perspectives and relationships between ‘stakeholder’ groups in the field of primary care and highlight the ways in which such relationships affect research in this area. The development of a primary care research project concerned with osteo-arthritis of the knee (the OAK project) is used as an exemplar of these stresses and we suggest ways in which the difficulties encountered may be overcome.
Keywords: Primary Care Research; Research Methodology